The Impact of Proficiency of Marketing Activities and Value Proposition Innovation on New Intelligent Products' Performance - Shashishekar, M. S.; Anand, Sandip (Indian Journal of Marketing, 2019)
Industrial products' manufacturing businesses are experiencing a change due to emerging need for intelligent products. Intelligent products are a new archetype of products having two layers. The first layer contains the classical hardware products augmented with intelligence on second layer. Intelligent products have a built in human-machine interface to interact with end users. Development and monetization of new intelligent products is a challenge as they subtly move the product business towards the solution business. Hence, it is critical to understand the determinants influencing new intelligent product performance in the market. The study synthesized the literature related to classical, intelligent products that identified marketing activities' proficiency and value proposition innovation as key variables critical for new intelligent product performance. The study was conducted during the year 2018–2019, collected data from 54 respondents having managed development and monetization of 42 new intelligent products launched during the years 2011-2017 belonging to 32 business units. It empirically validated the structural relationships between marketing activities' proficiency, value proposition innovation, and new intelligent product performance. The study deciphered that marketing activities' proficiency influenced the new intelligent product performance through value proposition innovation. It offered an empirical framework to attain unique value propositions and superior new intelligent product performance. The study suggested the practitioners to deploy a mechanism integrated with marketing activities and value proposition innovation to evolve unique value propositions. It also offered a unique framework of marketing activities' proficiency and value proposition innovation in the context of new intelligent product performance for further investigation by academicians.